ANALISIS STRUKTUR KEPEMILIKAN, CSRD, STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN DAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SUB SEKTOR KONSTRUKSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sari, Ananta Kumala; Hwihanus, Hwihanus (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to examine the effect of ownership structure, corporate social responsibility disclosure on firm value with financial performance and earnings management as intervening variables in construction sub-sector companies listed on the Indonesia Stock Exchange. The research method used is descriptive quantitative type because it uses statistical processes and analysis to calculate numerical data. The object of this research is construction sub-sector companies listed on the Indonesia Stock Exchange in 2019-2023. The sample was selected using a purposive sampling approach using documentation techniques sourced from the official website of the Indonesia Stock Exchange or the website of each company in order to obtain annual report data and sustainability reports that have been published by the company. The limitations of this study also include the following: first, the sample is limited to the construction subsector; second, the research period is only five years (2019-2023); and third, only a few construction subsector companies include the GRI index table. The results of this study there are 2 accepted hypotheses and 9 hypotheses that are not accepted including: ownership structure has no significant effect on financial performance, ownership structure has no significant effect on earnings management, ownership structure has no significant effect on firm value, CSRD has no significant effect on financial performance, CSRD has no significant effect on earnings management, capital structure has a significant effect on financial performance, capital structure has no significant effect on earnings management, capital structure has no significant effect on firm value, CSRD has no significant effect on firm value, financial performance has no significant effect on firm value, and earnings management has no significant effect on firm value.